Faktor-faktor yang mempengaruhi profitabilitas pada perusahaan sektor pertambangan yang terdaftar di Bursa Efek Indonesia tahun 2020-2022 - Kurniawan, Aan; Maryono, Maryono (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The mining sector plays a vital role in stimulating economic growth across various nations, including Indonesia. According to data provided by the Ministry of ESDM, coal production saw a decline to 558 million tons in 2020 had repercussions on both the financial performance and net earnings of mining companies, consequently impacting their overall profitability. Therefore, this study seeks to investigate and analyze the factors that influence the profitability of mining sector firms listed on the Indonesia Stock Exchange (IDX) during the period from 2020 to 2022. The research use qantitative method. The sampling method adopted is purposive sampling. The analytical techniques encompass descriptive statistics, normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, multiple linear regression analysis, coefficient of determination tests, F tests, and T tests, all conducted using SPSS 25 for Windows. The findings indicate that firm size and total asset turnover positively and significantly influence profitability, whereas leverage has a significant negative impact on profitability. Surprisingly, liquidity was found to have no significant effect on profitability. These results suggest that there is room for improvement in the management of company assets, highlighting the need for companies to focus on enhancing their asset management capabilities to foster sustained growth.